Metodologi Hadits di Era Modern: Urgensi Kritik Sanad dan Matan sebagai Fondasi Keilmuan Islam yang Otentik - Abdul Azis; Hadrian Nur; Muhammad Nasir; Ahmad Supriadi (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article examines the methodology of isnad (sanad) and matn criticism in hadith studies as a scientific instrument to verify the authenticity of prophetic traditions. Hadith represents the second source of Islamic law after the Qur'an; therefore, its validity must be ensured through systematic critical mechanisms. Isnad criticism focuses on the chain of transmission, encompassing continuity of narration (ittishal al-sanad), moral integrity ('adalah) and precision (dhabt) of narrators, and evaluation through the sciences of jarh wa ta'dil and rijal al-hadith. Meanwhile, matn criticism examines the textual substance of hadith through its conformity with the Qur'an, stronger traditions, linguistic analysis, historical context (asbab al-wurud), and detection of shadhdh and 'illah. This study employs a library research approach with descriptive-analytical methods applied to classical sources and contemporary scholarly journals. The findings indicate that classical and contemporary methods are complementary rather than contradictory. Their integration produces a comprehensive methodological framework relevant to modern academic contexts, particularly for students of Islamic Education Management who require a valid and accountable hadith knowledge base.